Precise Short Sequence Insertion in Zebrafish Using a CRISPR/Cas9 Approach to Generate a Constitutively Soluble Lrp2 Protein - Collery, Ross F.; Link, Brian A. (Frontiers in Cell and Developmental Biology, 2019)
Mutations in LRP2 are associated with buphthalmic eye enlargement, myopia and other nonocular symptoms. LRP2 is a large transmembrane receptor expressed on absorptive epithelia where it binds many extracellular ligands to control several signaling pathways. Though studies have clearly shown that absence of LRP2 protein causes these phenotypes, and that overexpression of individual LRP2 domains can exacerbate null LRP2 eye enlargement, the relationship between soluble LRP2 fragments and full-length membrane-bound LRP2 is not completely understood. Here we use a CRISPR/Cas9 approach to insert a stop codon cassette into zebrafish Lrp2 to prematurely truncate the protein before its transmembrane domain while leaving the entire extracellular domain intact. The resulting mutant line will be a useful tool for examining Lrp2 function in the eye, and testing hypotheses regarding its extracellular processing.